Effects of guanidinoacetic acid supplementation on zootechnical performance and some biometric indices in broilers challenged with T3-Hormone - Shady Khalil; Ahmed A. Al-Sagan; Hossam A. Abdellatif; Abdelbary Prince; Ramadan El-Banna (Italian Journal of Animal Science, 2021)
The objective was to elucidate the effects of dietary guanidinoacetic acid (GAA) supplementation on broiler performance, serum enzymes, oxidative biomarkers, mitochondrial activities, carcase traits, gross lesion of cardiac muscle and liver histopathology in broilers challenged with T3-hormone. A total-of-192 one-day-old mixed sexed broilers were randomly assigned in a two factorial design, including two dietary treatments; control diet supplemented with or without T3-hormone (1.5 ppm) and GAA diet (0.06%) supplemented with or without T3-hormone (1.5 ppm). Each group was subdivided into eight replicates. Results showed interactions between GAAxT3-hormone. GAA diet significantly mitigated the negative effect of T3-hormone on serum total creatine kinase (CK), cardiac muscle (CK-MB), liver malondialdehyde (MDA) and superoxide dismutase (SOD), mitochondrial activities of cardiac muscle and liver histopathological lesion. In conclusion, GAA at a rate of 0.06% may have the potential to mitigate the negative effect of dietary T3-hormone but could not reduce the ascites mortality at such inclusion rate.HIGHLIGHTS GAA protected heart muscle. GAA mitigated the oxidative radicals in T3-hormone challenged birds. GAA modulated the mitochondrial activities in T3-hormone challenged birds.